Effect of one dose of ceftriaxone during endotracheal intubation on the incidence of aspiration pneumonia in cerebral hemorrhage patients: A randomized, controlled, double-blind clinical study protocol - Xinyan Liu; Qizhi Wang; Yang Bi; Yanru Yue; Xuan Song (PLoS ONE, 2025)
Introduction Patients with cerebral hemorrhage often require a tracheal intubation to protect the airway and maintain oxygenation. Due to the use of analgesic and sedative drugs during endotracheal intubation and the opening of the glottis may easily cause aspiration pneumonia. Ceftriaxone is a semi-synthetic third-generation cephalosporin with strong antimicrobial activity against most gram-positive and gram-negative bacteria. It can effectively prevent and treat aspiration pneumonia. Methods and analysis This is a prospective, randomized, controlled, double-blind clinical study. Patients with intracerebral hemorrhage (ICH) undergoing endotracheal intubation in Dong E Hospital of Shandong Province from April 2023 to April 2025 will be enrolled and randomly assigned to the intervention group or control group. The intervention group will be treated using 100mL 0.9% sodium chloride with 2g ceftriaxone intravenously over the course of one hour beginning within two hours after endotracheal intubation. The control group will be given 100mL 0.9% sodium chloride injection intravenously of the course of one hour beginning within two hours after endotracheal intubation. The primary outcome is the incidence of aspiration pneumonia within 48 hours after endotracheal intubation. Secondary outcomes include: intensity of antimicrobial use, length of hospital stay, duration without mechanical ventilation, and 28-day mortality. Discussion The primary objective of this study is to explore whether a single dose of ceftriaxone administered during endotracheal intubation in patients with ICH reduced the incidence of pneumonia within 48 hours and provide evidence for the prevention of aspiration pneumonia in patients with ICH with endotracheal intubation. Trial registration The trial is registered at the Chinese Clinical Trial Registry: ChiCTR2200066837. Registered on December 19, 2022.